Self-emulsifying drug delivery system of black seed oil with improved hypotriglyceridemic effect and enhanced hepatoprotective function. (March 2021) - Halder, Shimul; Islam, Amena; Muhit, Md. Abdul; Shill, Manik Chandra; Haider, Syed Shabbir
Graphical abstract: Highlights: Black seed oil (BSO)-loaded self-emulsifying drug delivery system (SEDDS-BSO) was successfully developed. SEDDS-BSO led to enhanced hepatoprotective effects compared with BSO in rats. SEDDS-BSO suppressed increase in plasma TG level more effectively than BSO in rats. Abstract: Black Seed Oil (BSO), obtained from the seeds of black cumin ( Nigella sativa ), has antioxidant, anti-inflammatory, and hepatoprotective effects. The present study was aimed to develop a self-emulsifying drug delivery system (SEDDS) of BSO, to improve hypotriglyceridemic and hepatoprotective function. SEDDS-BSO formed fine micelles with a mean droplet size of 183 nm and improved the dispersion behavior of BSO in water as evidenced by at least 2.6-fold higher dispersibility compared with BSO. In the CCl4 -treated rat model of acute hepatic injury, SEDDS-BSO (10 mg-BSO/kg, p.o .) led to 91.7% and 86.8% reductions of alanine aminotransferase and aspartate aminotransferase, respectively, suggesting that SEDDS-BSO could attenuate hepatotoxicity compared to BSO. In addition, repeated oral administration of SEDDS-BSO (10 mg-BSO/kg, p.o. ) for 7 days had a potent hypotriglyceridemic effect on rats with corn-oil-induced hypertriglyceridemia compared to BSO. Therefore, the SEDDS approach might be an efficacious dosage option to enhance the nutraceutical properties of BSO.